2021
DOI: 10.3390/microorganisms9020293
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Wall: Characterization of the Multiheme Cytochromes Involved in the Extracellular Electron Transfer Pathway of Thermincola ferriacetica

Abstract: Bioelectrochemical systems (BES) are emerging as a suite of versatile sustainable technologies to produce electricity and added-value compounds from renewable and carbon-neutral sources using electroactive organisms. The incomplete knowledge on the molecular processes that allow electroactive organisms to exchange electrons with electrodes has prevented their real-world implementation. In this manuscript we investigate the extracellular electron transfer processes performed by the thermophilic Gram-positive ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…The challenge of bridging the distance through the multilayer cell wall could be overcome by formation of polymeric structures of CwcA similar to OmcS in G. sulfurreducens . Evidence, for the latter stems from bioinformatic homology modeling of CwcA along the polymeric structure of OmcS and the fact that it was not possible to stabilize the protein in a soluble form in a purification attempt (Faustino et al 2021 ). The midpoint redox potentials of the heme proteins are overlapping and are in a range between + 100 mV and − 300 mV vs SHE.…”
Section: The Biochemistry Of Microbial Electron Transfer To Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge of bridging the distance through the multilayer cell wall could be overcome by formation of polymeric structures of CwcA similar to OmcS in G. sulfurreducens . Evidence, for the latter stems from bioinformatic homology modeling of CwcA along the polymeric structure of OmcS and the fact that it was not possible to stabilize the protein in a soluble form in a purification attempt (Faustino et al 2021 ). The midpoint redox potentials of the heme proteins are overlapping and are in a range between + 100 mV and − 300 mV vs SHE.…”
Section: The Biochemistry Of Microbial Electron Transfer To Anodesmentioning
confidence: 99%
“…Diamonds indicate the number of heme cofactors in the respective c -type cytochromes. Scheme modified from Faustino et al ( 2021 ) …”
Section: The Biochemistry Of Microbial Electron Transfer To Anodesmentioning
confidence: 99%
“…Based on the electrochemical characterization, only ImdcA and PdcA were studied in support of the pathway. Another protein, CwcA, could not be stabilized in solution, and based on the homology with the OmcS, a structural model for CwcA was developed, providing a molecular perspective into the mechanisms of electron transfer across the peptidoglycan layer in Thermincola (Faustino et al 2021).…”
Section: Analysis Of Extracellular Respiration Pathwaymentioning
confidence: 99%
“…Biological components such as cytochrome C, riboflavin, conductive nanowires, and some natural organic substances (e.g., humic substances) can naturally act as electron shuttles to facilitate EET due to their excellent dielectric capacity and unique biochemical properties ( Reguera et al, 2005 ; Sutton and Sposito, 2005 ; Watanabe et al, 2009 ; Dang et al, 2016 ; Faustino et al, 2021 ). For example, analysis of the structure of the transmembrane protein complex of the extracellular membrane revealed that protein metal reducing AB (MtrAB) can act as an electron transfer channel to transfer intracellular electrons to the extracellular electron receptor by means of MtrC, which is tightly bound to it ( Edwards et al, 2020 ); Geobacter sulfurreducens usually achieves long-distance electron transfer by means of its conductive nanowires in direct contact with the electron receptor.…”
Section: Introduction To Electron Shuttlementioning
confidence: 99%